Omah Rojolele: Pelestarian Budaya Agraris dan Pemberdayaan Integratif Interkonektif Desa Delanggu Klaten - Gusti, Kinanthi Ing; Jingga, Lintang Antarikza; Prasetiya, Rio Dwi; Hapsari, Annisa Nur; Hafiya, Aqila; Safitri, Diana Lutfia Nur; Darwis, Gusti Putu Astasidi Ahmad; Maghfiroh, Lailil; Permadi, Muhammad Wildan Dimas; Fawwaz, Prabu Lingga Wijaya; Kedaton, ⁠Prameswari Bunga; Ramadhani, Safitri; Adkia, Tauba Zaka; Ramadhan, Della Amanda; Trengginas, Surya; Rustamaji, Muhammad; Indreswari, Rysca (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Delanggu Village is well-known for its agricultural success, particularly as a producer of the Rojolele rice variety. Delanggu Village, which preserves historical values in the agricultural sector, has the potential for cultural preservation through various artistic events in the form of a farming cultural celebration called the Mbok Sri Festival. However, the preservation and strengthening of agricultural culture has only been limited to the Mbok Sri Festival, which is held once a year. As a result, the establishment and reinforcement of agrarian culture in Delanggu Village is not ideal. As a result, new value developments are required to maximize the preservation of agrarian culture and time-limited tourist trips to Delanggu Village. Based on these issues, the PPK Ormawa KSP